Gedrukte kaarten van Europa vóór Ortelius. Een toevoegsel - H.A.M. van der Heijden (Belgeo)
This article is a concise and elucidating survey of De oudste gedrukte Kaarten van Europa (The oldest printed maps of Europe), Alphen aan den Rijn, Canaletto, 1992. In this book forty general maps of Europe and seven maps of Europe in the shape of a royal lady (Virgo Europa) are described, depicted and supplied with comment. All forty geographical maps belong to the period before Ortelius. They are for the greater part in several sheets and engraved in wood or copper with much geographical and artistical skill. They rather differ, though, from reality, especially the northern part of Europe. In this respect the map of Europe, which Abraham Ortelius inserted in his first atlas Theatrum Orbis Terrarum of 1570 meant a great improvement. Therefore, in the cartographical reproduction of the European continent Ortelius’ map “Europae” meant a definitive turn.